Transient inhibition of lysosomal functions potentiates nucleic acid vaccines - Wang, Chunxi; Karlsson, Amelia; Oguin, 3rd, Thomas H; Macintyre, Andrew N; Sempowski, Gregory D; McCarthy, Kevin R; Wang, Yifei; Moody, M Anthony; Yuan, Fan (Proceedings of the National Academy of Sciences - PNAS, 2023)
Nucleic acid vaccines have shown promising results in the clinic against infectious diseases and cancers. To robustly improve the vaccine efficacy and safety, we developed an approach to increase the intracellular stability of nucleic acids by transiently inhibiting lysosomal function in targeted tissues using sucrose. To achieve efficient and localized delivery of sucrose in animals, we designed a biomimetic lipid nanoparticle (LNP) to target the delivery of sucrose into mouse muscle cells. Using this approach, viral antigen expression in mouse muscle after DNA vaccination was substantially increased and prolonged without inducing local or systemic inflammation or toxicity. The same change in antigen expression would be achieved if the vaccine dose could be increased by 3,000 folds, which is experimentally and clinically impractical due to material restrictions and severe toxicity that will be induced by such a high dose of nucleic acids. The increase in antigen expression augmented the infiltration and activation of antigen-presenting cells, significantly improved vaccine-elicited humoral and T cell responses, and fully protected mice against the viral challenge at a low dose of vaccine. Based on these observations, we conclude that transient inhibition of lysosome function in target tissue by sucrose LNPs is a safe and potent approach to substantially improve nucleic acid-based vaccines.